Parental decision‐making on utilisation of out‐of‐home respite in children's palliative care: findings of qualitative case study research ‐ a proposed new model. (7th November 2015) - Ling, J.; Payne, S.; Connaire, K.; McCarron, M.
Summary: Background: Respite in children's palliative care aims to provide a break for family's from the routine of caring. Parental decision‐making regarding the utilisation of out‐of‐home respite is dependent on many interlinking factors including the child's age, diagnosis, geographical location and the family's capacity to meet their child's care needs. A proposed model for out‐of‐home respite has been developed based on the findings of qualitative case study research. Methods: Utilising multiple, longitudinal, qualitative case study design, the respite needs and experiences of parents caring for a child with a life‐limiting condition were explored. Multiple, in‐depth interviews were undertaken with the parents identified by a hospital‐based children's palliative care team. Data were analysed using thematic analysis. Each individual case consists of a whole study. Cross‐case comparison was also conducted. Results: Nine families were recruited and followed for two years. A total of 19 in‐depth interviews were conducted with mothers and fathers (one or both) caring for a child with a life‐limiting condition in Ireland. Each family reported vastly different needs and experiences of respite from their own unique perspective. Cross‐case comparison showed that for all parents utilising respite care, regardless of their child's age and condition, home was the location of choice. Many interlinking factors influencing these decisions included: past experience of in‐patient care, and trust and confidence in care providers. Issues were raised regarding the impact of care provision in the home on family life, siblings and the concept of home. Conclusion: Respite is an essential element of children's palliative care. Utilisation of out‐of‐home respite is heavily dependent on a number of interlinked and intertwined factors. The proposed model of care offers an opportunity to identify how these decisions are made and may ultimately assist in identifying the elements of responsive and family‐focused respite that are important to families of children with life‐limiting conditions.